Accounting for Non-Accounting Students - Dyson, J. R. (John Richard), 1939- (Harlow : Financial Times Prentice Hall, 2001)
This book is traditional in approach and covers both financial & management accounting. This edition has been streamlined: long & difficult chapters have been simplified, case studies have been added & further subdivisions make the book more flexible.
Previous ed.: 1997.
Includes index.
Keywords: Accounting; Accounting -- Problems, exercises, etc; Finance and Accounting